Effect of fluvalinate on the expression profile of circular RNA in brain tissue of Apis mellifera ligustica workers - Xueqing, Shan; Delong, Lou; Guizhi, Wang; Yunhan, Fan; Liuxu, Yang; Tianle, Chao (Frontiers in Genetics, 2023)
Fluvalinate was widely used in apiculture as an acaricide for removing Varroa mites, but there have been growing concerns about the negative effects of fluvalinate on honeybees in recent years. Previous research revealed changes in the miRNA and mRNA expression profiles of Apis mellifera ligustica brain tissues during fluvalinate exposure, as well as key genes and pathways. The role of circRNAs in this process, however, is unknown. The goal of this study was to discover the fluvalinate-induced changes in circRNA expression profiles in Apis mellifera ligustica worker brains. A total of 10,780 circRNAs were detected in Apis mellifera ligustica brain tissue, 8 of which were differentially expressed between at least two of the four time periods before and after fluvalinate administration, and 6 circRNAs were experimentally verified to be structurally correct and their expression patterns were consistent with transcriptome sequencing results. Further ceRNA analysis revealed that five DECs (novel_circ_012139, novel_circ_011690, novel_circ_002628, novel_circ_004765, and novel_circ_010008) were primarily involved in apoptosis-related functions by competitive binding with miRNAs. This study discovered changes in the circRNA expression profile in Apis mellifera ligustica brain tissue caused by fluvalinate exposure, and it provides a useful reference for the biological function study of circRNAs in Apis mellifera ligustica.